(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The present paper studies the issues of improving the reliability of the working bodies of hammer crushers. This machine is widely used for grinding grain material in animal husbandry and the processing industry. The main wear element of such crushers is the hammers and disks to which they are attached. To study the strength characteristics of these parts, a technique and algorithm for studying the stress-strain state of the hammer crusher disc employing the finite element method (FEM) using computer simulation software products were developed. The mathematical apparatus of finite element method simplifies the model construction where the stress-strain state must be explored. Finite element method provides solutions in the form of stress and deformation fields in almost any cross-section of structural parts. The express analysis module of the APM FEM COMPASS system was used as the software for this work. The implementation of finite element methodwill reduce the metal intensity of the equipment, increase the reliability of its operation and reduce the cost, improve the quality of the feed produced. The results of the study showed that the maximum stresses occur on the surface creating the internal holes in the place of attachment of the disc to the shaft, but the stresses that occur there remain within the normal range.